2015
DOI: 10.1080/10803548.2015.1028230
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership, social support and their role in workplace bullying and its mental health consequences

Abstract: The aim of this study was to show how authentic leadership is related to social support and exposure to workplace bullying and how these variables are related to mental health. For our sample of 820 office workers employed in different Polish organizations and sectors, social support from supervisors moderated the relationship between authentic leadership and workplace bullying. Social support from co-workers moderated the relationship between workplace bullying and mental health and authentic leadership moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…A review of the existing research highlights the positive effect of authentic leadership on the sense of fulfilment of basic needs by employee groups and on work engagement [15,16,31]. Authentic leadership reduces the likelihood of professional burnout and the desire to quit work [32], reduces bullying [33], and helps create an active approach to conflict management in organizations [34]. A link exists between authentic leadership and satisfaction with supervisors [29] and work engagement [13,16,35].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing research highlights the positive effect of authentic leadership on the sense of fulfilment of basic needs by employee groups and on work engagement [15,16,31]. Authentic leadership reduces the likelihood of professional burnout and the desire to quit work [32], reduces bullying [33], and helps create an active approach to conflict management in organizations [34]. A link exists between authentic leadership and satisfaction with supervisors [29] and work engagement [13,16,35].…”
Section: Introductionmentioning
confidence: 99%
“…There are also few studies investigating factors that may protect individuals against the effects of workplace bullying. Some studies have looked at support from co-workers (see for example Rousseau et al 2014;Warszewska-Makuch et al 2015;Van den Brande et al 2016) and supportive leadership (see for example Gardner et al 2013;Clausen et al 2019) as protective factors. However, to our knowledge no previous studies have looked at the effects of support from these two sources in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Looking only at co-worker support, a Polish study (Warszewska-Makuch et al 2015) reported that the negative association between workplace bullying and mental health was moderated by support from co-workers. The positive effects of co-worker support were also demonstrated by Van den Brande et al (2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luthans & Walumbwa, 2004) to build up authentic leadership (AL) in their followers (Ilies, Morgeson, & Nahrgang, 2005) for constructive and optimistic decision-making behaviors (Luthans & Youssef, 2007). Authentic leadership is a way of learning about self, and self-information; understanding and thoughtfulness to others' positioning and a methodological cleverness that proceeds to the interaction of management actions (Warszewska-Makuch, Bedyńska, & Żołnierczyk-Zreda (2015). Authentic leaders are always cognizant of their natural abilities, recognize their shortcomings and work hard to overcome loopholes (Hassan & Ahmed, 2011).…”
Section: Introductionmentioning
confidence: 99%